2016
DOI: 10.1007/s11356-016-6373-2
|View full text |Cite|
|
Sign up to set email alerts
|

Removing heavy metals from Isfahan composting leachate by horizontal subsurface flow constructed wetland

Abstract: Composting facility leachate usually contains high concentrations of pollutants including heavy metals that are seriously harmful to the environment and public health. The main purpose of this study was to evaluate heavy metals removal from Isfahan composting facility (ICF) leachate by a horizontal flow constructed wetland (HFCWs) system. Two horizontal systems were constructed, one planted with vetiver and the other without plant as a control. They both operated at a flow rate of 24 L/day with a 5-day hydraul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 46 publications
1
11
0
Order By: Relevance
“…High rate of heavy metal of Cu (96 %), Zn (95 %), (Fe 93) and Cr (91 %) in the present study as compared to the Typha latifoliya, Myriophylhum aquaticum , Ludwigina palustris , Eichhornia crassipes , Schoenoplectus californicus , Cyperus papyrus and Phragmites australis reported by Crites et al (1997), Lim et al (2003), Kamal et al (2004), Nelson et al (2006), Maine et al (2009), Zhao et al (2011), Bakhshoodeh et al (2016), Mustapha et al (2018) and Hamad (2020) which indicates C. indica is the high potential for heavy metal removal and can be strongly used for industrial wastewater. However, other researchers have reported on successful wastewater treatment and pollution control using C. indica ‐based CWs (Calheiros et al, 2015; Cui et al, 2010; Samal et al, 2017; Ventura et al, 2021).…”
Section: Resultssupporting
confidence: 52%
See 1 more Smart Citation
“…High rate of heavy metal of Cu (96 %), Zn (95 %), (Fe 93) and Cr (91 %) in the present study as compared to the Typha latifoliya, Myriophylhum aquaticum , Ludwigina palustris , Eichhornia crassipes , Schoenoplectus californicus , Cyperus papyrus and Phragmites australis reported by Crites et al (1997), Lim et al (2003), Kamal et al (2004), Nelson et al (2006), Maine et al (2009), Zhao et al (2011), Bakhshoodeh et al (2016), Mustapha et al (2018) and Hamad (2020) which indicates C. indica is the high potential for heavy metal removal and can be strongly used for industrial wastewater. However, other researchers have reported on successful wastewater treatment and pollution control using C. indica ‐based CWs (Calheiros et al, 2015; Cui et al, 2010; Samal et al, 2017; Ventura et al, 2021).…”
Section: Resultssupporting
confidence: 52%
“…The literature revealed that macrophytes in CWs can accumulate heavy metals from wastewater in their stems, leaves and rhizomes/roots, indicating that they can be used as plants to remove excess heavy metals from wastewater (Anning et al, 2013; Bakhshoodeh et al, 2016; Calheiros et al, 2008; Peverly et al, 1995). Vodyanitskii and Shoba (2015) stated that macrophytes play a critical role in wetland geochemistry, further extensive root system, highly productive biomass, immobile nature and tolerance to toxicity; macrophytes can generally acquire significant quantities of heavy metals from water and sediments (Ventura et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…High levels of heavy metals are highly toxic to aquatic animals, and they can also be accumulated in the muscles of fish or shrimps, which may cause an adverse impact on food safety [55,56]. CW has been applied extensively for the removal of heavy metals from urban sewage through different mechanisms [57]. The capacity of wetland plants for heavy metals removal is shown in many studies [58,59].…”
Section: Discussionmentioning
confidence: 99%
“…In the agricultural industry, harvesting and post-harvesting activities generate large quantities of solid waste [73]. Agricultural waste can offer a good alternative to conventional insulation materials: they are renewable annually and compostable, and they naturally have low thermal conductivity [74]. Total yearly agricultural by-product that has been produced in EU-27 in 2000-2002 was 457 million tonnes, about half of which (215 million tonnes) was accepted as by-product [75].…”
Section: Agricultural Solid Waste Into Building Insulation Materialsmentioning
confidence: 99%